(untitled) (Ameghiniana, 2013)
The most ancient Cardiatheriinae (Rodentia, Hydrochoeridae) from the Arroyo Chasico? Formation (Lower Pliocene) are described. Besides an almost complete mandible most of the material so far known are isolated cheek-teeth, which represent at least two species: Procardiatberiurn chasicoense n. sp. and ¿Cardiatherium dubium. Its relationships and its.bearing on the problem of the Hydrochoerinae differentiation are analyzed.